Google Home Mini Sebagai Sistem Pengontrol Perangkat Elektronik Berbasis Voice Recognition - Thoriq Dharmawan; Suci Aulia; Dadan Nur Ramadan (eProceedings of Applied Science, 2019)
Abstract— Voice recognition is a process of capturing words spoken through a microphone and then turning them into digital data. The application of voice recognition can be found on Google Home Mini. With this technology, it was tested the implementation of a system with voice recognition method using Google Home Mini combined with an IoT platform so that it can control electronic equipment through voice commands. Intisari— Voice recognition merupakan sebuah proses menangkap kata - kata yang diucapkan melalui microphone lalu mengubahnya menjadi data digital. Penerapan voice recognition bisa kita jumpai pada Google Home Mini. Dengan adanya teknologi tersebut, maka diujicobakan pengimplementasian suatu sistem dengan metoda voice recognition menggunakan Google Home Mini yang dikombinasikan dengan sebuah platform Iot sehingga dapat mengendalikan peralatan elektronik melalui perintah suara. Kata Kunci— Voice Recognition, Audio Processing, Google Home Mini